Fertilizer Cost Build-up in Tanzania and policy options for increasing smallholder farmers’ access - Mwaijande, Francis (International Journal of Scientific Research and Management (IJSRM), 2019)
Fertilizer price cost build up in Tanzania limits 96.5% of the smallholder farmers access to fertilizer that deter agricultural productivity and the goal for attaining food security. The objective of the paper was to examine strategies for addressing fertilizer price build up in Tanzania that would increase fertilizer use and create demand by smallholder farmers. We use secondary data from the reviewed literature on factors for price build up in Tanzania. The study adopts the supply chain analysis from the source of origin, importation, shipping costs, port service charges, quantity procured, methods of procurement, blending and packaging, as well as means of transportation used. The key determinants in the chain include the Cost, Insurance and Freight (CIF), port charges, port handling costs, bagging, storage fees and means of transportation. The most two significant drivers for the fertilizer price build up is the procurement method and means of transportation that seem to significantly increase farm gate prices. It has been established that price build up is a function of quantity imported due to economies of scale; that is to say importing small quantities pushes buyers to pay high prices for the product and shipping expenses. The infrastructural factors for fertilizer price build up are associated with the mode of transportation as either road haulage or railways use. It has been established that transporting bulky fertilizers to various destinations by road is more expensive when relatively compared with railway transportation. The paper, therefore recommends for policy change that emphasize bulky fertilizer transportation by railways and monitor its implementation.